Strengthening facilitation competencies in development: processes, challenges and lessons of a learning alliance to develop facilitators for local community engagement - Lefore, Nicole (2015)
Effective facilitation enables farmer-based water user organizations to analyse contextual issues, identify causal links, formulate clear challenges, develop partnerships with stakeholders, and innovate and implement solutions. However, facilitation is often provided by international partners, such as advanced research institutions or non-governmental organisations (NGOs). The reliance on external consultants to facilitate innovation and change processes creates risks for sustainability. This article provides an overview of a capacity development initiative for facilitation of change in the agriculture water sector in Africa. It focuses on the case study of the Improved Management for Agricultural Water in East and Southern Africa (IMAWESA) network’s learning alliance on facilitating community engagement. The IMAWESA learning alliance sought to build competency on facilitation methods and tools at national and sub-national levels within and across agricultural water management projects. The paper primarily seeks to address questions related to the sustainability of facilitated processes and the effectiveness of capacity development methods to train facilitators and thus strengthen local facilitation.